Effects of chronic beta-receptor blocker treatment on cardiac high-energy phosphate metabolism in heart failure - Neubauer, S (2000)
In heart failure, chronic therapy with beta-receptor blocking agents improves cardiac performance and prolongs survival, but the exact mechanisms whereby these compounds exert such beneficial effects remain unclear. One hypothesis is that beta-blockers improve the energetic balance of the heart and act, at least in part, by preserving high-energy phosphate metabolism. In experimental heart failure caused by chronic coronary ligation in the rat, the beta-blocker bisoprolol significantly improves cardiac function in parallel to preservation of phosphocreatine stores and intracellular ATP transfer rates, suggesting improved cardiac energetics as one mechanism of action. Clinical evidence on energetic effects of beta-blockers is still only anecdotal. We showed in four patients with dilated cardiomyopathy that the phosphocreatine/ATP ratio, measured by 31p-MR spectroscopy, increases during chronic metoprolol therapy. Currently, a larger systematic placebo-controlled clinical trial of the functional and energetic effects of bisoprolol in dilated cardiomyopathy, followed sequentially by MR imaging and spectroscopy, is underway, which, when completed, should reveal whether beta-blockers in fact preserve high-energy phosphate metabolism in human heart failure.